A comparative study on the practical utilization of iron tailings as a complete replacement of normal aggregates in dam concrete with different gradation. (20th February 2019) - Lv, Xingdong; Shen, Weiguo; Wang, Lei; Dong, Yun; Zhang, Jianfeng; Xie, Zhiqiang
Abstract: Tailing, which is a type of industrial solid waste, is widespread in China with low utility. How to effectively make full use of tailing has been attracted great attention from the entire society. The goal of this study is to provide a possibility to utilize the tailings as a complete replacement of normal aggregates in dam concrete projects, and the comparison of the influence of tailing aggregate (TA) and natural aggregate(NA) on dam concrete performances are investigated. The fresh concrete properties, mechanical properties, dimensional stability, frost-resistant and thermal performance are discussed in this paper. The results show concrete prepared with TA has a good workability but it indeed exhibits many differences compared to concrete with NA. The TA concrete has a higher specific gravity and water consumption than NA concrete. The TA concrete has the similar mechanical properties, ultimate tensile strain, compressive elastic modulus and frost-resistant performance compared to NA concrete at the fixing approximate cementitious materials consumption. In addition, TA concrete has a relative lower temperature conduction, heat conduction and linear expansion coefficient than NA concrete at the same condition. TA concrete is superior to NA concrete, especially it has a superior thermal performance. More importantly, utilization of TA as a complete replacement of normal aggregates has significant environmental and economic benefits. Highlights: Using TA as a complete replacement of NA in dam concrete which is very new research filed. The comprehensive comparisons of TA and NA on concrete performances are investigated. TA as a complete replacement of NA has significant environmental and economic benefits.